Alignment of nanostructured tripeptide gels by directional ultrasonication1. Issue 40 (18th May 2015) - Pappas, Charalampos G.; Frederix, Pim W. J. M.; Mutasa, Tapiwa; Fleming, Scott; Abul-Haija, Yousef M.; Kelly, Sharon M.; Gachagan, Anthony; Kalafatovic, Daniela; Trevino, Jacob; Ulijn, Rein V.; Bai, Shuo
<x xml:space="preserve">Abstract</x> We demonstrate an in situ ultrasonic approach to generate anisotropic organo- and hydrogels consisting of oriented tripeptides self-assembled structures.